Hubungan Kadar Malondialdehida (MDA) Serum dan Fraksi Ejeksi Ventrikel Kiri pada Pasien Hemodialisis Reguler - Amir, Teguh Setiadi; Indrajaya, Taufik; Ali, Zulkhair (Jurnal Penyakit Dalam Indonesia, 2026)
Introduction. Malondialdehyde (MDA) is a marker of oxidative stress that is elevated in chronic kidney disease (CKD) patients undergoing regular hemodialysis. Oxidative stress can affect cardiac function especially left ventricular function. This study aimed to evaluate the relationship between serum MDA levels with left ventricular function in regular hemodialysis patients at Dr. Mohammad Hoesin Genaral Hospital, Palembang. Methods. This study was an analytic observational study with a cross-sectional design conducted on regular hemodialysis patients in the Hemodialysis Installation of Dr. Mohammad Hoesin Genaral Hospital, Palembang. The MDA levels were examined from the serum of post-hemodialysis patients using ELISA method. Echocardiography was then performed to determine left ventricular function. Statistical analysis was performed using STATA version 15 with Spearman correlation and Chi-square tests. Results. Among 121 subjects, median serum MDA levels was 4.05 (0.68-27.21) μmol/L. Correlation analysis demonstrated a significant moderate negative correlation between serum MDA levels and LVEF (r = −0.38, p < 0.0001). Mann–Whitney analysis showed that patients with reduced LVEF had significantly higher MDA levels than those with normal LVEF (median: 10.035 vs. 3.112 μmol/L). Furthermore, elevated MDA levels were significantly associated with reduced LVEF, with patients having high MDA levels exhibiting a 4.8-fold greater odds of reduced LVEF (OR 4.826, 95% CI 1.611–17.310). Conclusions. Elevated serum MDA levels were significantly associated with impaired left ventricular function in patients with stage V CKD undergoing regular hemodialysis at Mohammad Hoesin General Hospital, Palembang. Patients with high serum MDA levels had a 4.8-fold higher odds of reduced LVEF than those with lower MDA levels.